(untitled) (Research, Society and Development, 2020)
Introduction: Assistive technology are devices, resources and processes that promote a significant improvement in the quality of life of people with disabilities. Due to the high values of prostheses and orthoses, additive manufacturing appears, which promotes prosthetic parts that fulfill their functions; promote functionality, and also facilitating access to these parts, since they are cheaper. Objective: to demonstrate through an experience report, the experiences carried out by a group of academics in the creation of low-cost orthotic devices, with the use of 3D technology within an extension project. Methodology: The present research is characterized as a descriptive research with characteristics of experience report. Results and discussions: the experiences that this project provided were important in the process of academic and professional training of extension workers, since there was contact in the production and construction of prosthetic parts, application of protocols, learning in specialized evaluation and knowledge about the 3D printer. Conclusion: The experiences of the 3D little hands project contributed significantly to successful experiences, which may open new ideas and new projects to help other people who need a foundation in the creation of similar projects in other regions.